PENGARUH KNOWLEDGE MANAGEMENT DAN SELF DEVELOPMENT TERHADAP JOB SATISFACTION MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR KARYAWAN PT PRIMA MULTI PERALATAN CABANG TPK BELAWAN - Dino Erivianto (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study aims to analyze and determine the influence of knowledge management and self development on job satisfaction through organizational citizenship behavior of employees. The study used a quantitative descriptive approach with a sample of 65 employees of PT Prima Multi Peralatan Branch TPK Belawan. Data collection techniques using questionnaires and data analysis techniques using the Partial Least Square-Structural Equestion Model (PLS-SEM). The results of testing from the concept framework in the form of the influence of knowledge management on job satisfaction, the influence of self development on job satisfaction, the influence of organizational citizenship behavior on job satisfaction, the influence of knowledge management on organizational citizenship behavior, the influence of self development on organizational citizenship behavior, the influence of knowledge management on job satisfaction through organizational citizenship behavior, the influence of self development on job Satisfaction through organizational citizenship behavior, expressed as all have a positive and significant influence .